DISPARITAS PUTUSAN HAKIM PIDANA BERKUALITAS YANG MENCERMINKAN RASA KEADILAN DALAM SISTEM HUKUM INDONESIA - Kusyandi, Adi; Yamin, Saefullah (Yustitia, 2023)
Republic of Indonesia as required in Article 24 of the Republic of Indonesia. Indonesia. Judges are free from any coercion and/or pressure from anyone in carrying out their judicial but are free to do whatever they want. The principle of freedom of judges refers to the independence or independence of the judiciary to provide objective and fair decisions. Indonesian judges understand and carry out the meaning of the freedom of judges by carrying out the main duties of judicial power in accordance with procedural law and applicable law, namely freedom of responsibility, corridors of freedom of order in applicable laws and regulations, freedom from government, and interests. groups, pressure groups, print media influence, electronic media, and influential individuals.